2014
DOI: 10.1021/ma402356z
|View full text |Cite
|
Sign up to set email alerts
|

Enormously Wide Range Cylinder Phase of Liquid Crystalline PEO-b-PMA(Az) Block Copolymer

Abstract: A series of amphiphilic liquid crystalline diblock copolymers, PEO m -b-PMA(Az) n , consisting of hydrophilic poly(ethylene oxide) and hydrophobic poly(methacrylate) moieties with side chains containing liquid crystalline (LC) azobenzene moieties, produced highly ordered microphaseseparated films with PEO cylinders aligned perpendicular to the smectic LC layer of azobenzene in the PMA(Az) matrix. In this paper, morphological phase diagrams of PEO m -b-PMA(Az) n diblock copolymers above and below the isotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Simultaneously, the azobenzene LC groups in the hydrophobic domains selforganize to form alignments vertical to hydrophilic domains, 39,49 which makes the cylindrical micelles more stable. Scheme 1 illustrates the proposed synthesis process.…”
Section: Formation Process Of Ordered Mesoporous Titaniamentioning
confidence: 99%
“…Simultaneously, the azobenzene LC groups in the hydrophobic domains selforganize to form alignments vertical to hydrophilic domains, 39,49 which makes the cylindrical micelles more stable. Scheme 1 illustrates the proposed synthesis process.…”
Section: Formation Process Of Ordered Mesoporous Titaniamentioning
confidence: 99%
“…52 Three kinds of block copolymers with different molecular weights of each segment, PEO40-b-PMA(Az)17, PEO114-b-PMA(Az)45, and PEO272-b-PMA(Az)94, were adopted to achieve the size control of the PPy nanowire array (characterization of these polymers is described in Figures S1b-S1d 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 nanowire diameter of 7 nm, a periodicity of 13 nm, and a density of 4.4 × 10 12 wires/in. 2 , which has been never achieved before.…”
Section: Feature Size Control Of Ppy Nanowire Arraymentioning
confidence: 99%
“…Several research studies have revealed the significant effects of LC ordering of the side-chains on the microphase separation due to homeotropic orientation of the liquid crystalline microdomains. [24][25][26][27][28] In contrast to the conventional non-LC block copolymers, the LC azobenzene mesogen-mesogen interaction functions as an additional elastic energy term (F LC ) in the expression of total free energy (F) of the PEO-b-PMA(Az) thin film system. PEO-b-PMA(Az), one of such block copolymers, consists of poly(ethylene oxide) (PEO) as a segment forming cylindrical microdomains, and poly(methacrylate) with azobenzene mesogens in the side chain (PMA(Az)) as a segment forming a matrix phase (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1). 27,28 Another advantage is the perpendicular orientation of the PEO hexagonal cylindrical microdomains to a substrate by just a thermal annealing process, which is due to homeotropic anchoring of the Az mesogens to the air/free interface. The total free energy of the system is given by the following equation.…”
Section: Introductionmentioning
confidence: 99%